Obesity is positively associated with dehydroepiandrosterone sulfate concentrations at 7 y in Chilean children of normal birth weight(1)(2)(3) - Corvalán, Camila (American Society for Nutrition, 2013)
Background: In low-birth-weight girls, obesity increases the risk of premature adrenarche and metabolic complications. However, the consistency of this association in normal-birth-weight children and its potential mediators remain unknown. Objectives: The objectives were to assess the associations between obesity indicators and dehydroepiandrosterone sulfate (DHEAS) at 7 y of age and to evaluate the role of hormonal markers on these associations. Design: We assessed in 969 participants (6.9 y; 48% girls; all Tanner I) in the Growth and Obesity Chilean Cohort Study the associations between DHEAS and weight, BMI, waist circumference (WC), waist-to-height ratio, skinfold thickness, and percentage total fat (bioimpedance) and determined whether these associations were related to insulin, insulin-like growth factor I (IGF-I), and leptin. We also compared BMI and height growth from 0 to 7 y of age in nonobese and obese children with normal and high DHEAS (≥75th percentile) at 7 y. Results: DHEAS concentrations were similar between girls (30.3 ±1.86 μg/dL) and boys (29.4 ±1.73 μg/dL) (P > 0.05); 17.3% of children were obese (BMI-for-age z score ≥2 SD). Adiposity indicators were positively and similarly associated with DHEAS [ie, BMI, β standardized regression coefficient: 0.23 (95% CI: 0.17, 0.29); WC, β standardized regression coefficient: 0.23 (95% CI: 0.16, 0.30)]; these associations were only partially related to IGF-I and leptin. Obese children had twice the risk of high DHEAS (OR: 2.16; 95% CI: 1.51, 3.09); at 7 y, obese children with high DHEAS were fatter and more centrally obese than their counterparts (P < 0.05), although their previous growth was similar (P > 0.05). None of the results differed by sex (P > 0.05). Conclusion: In children of normal birth weight, obesity is positively associated with DHEAS at 7 y of age.